Brand coolness effects on brand love, purchase intention and word of mouth: application to indonesian women modest sportswear - Dwikinanda, Irfan (2022)
This dissertation analyzes the effect of brand coolness on brand love, purchase intention, and word of mouth in Indonesian market applied to the modest sportswear. Considering the perceptions of Indonesians’ millennials and generation Z, this study contributes with another cultural dimension to the existent literature, which is focused on the western culture. As one of the most populated country in the world along with the highest Muslim population, Indonesian possesses a modest sportswear market with a huge potential to growth, as well as provides different perspective of culture and a specific type of product for the feminine target. The differences could be seen in its characteristic that covers most of the skin of the wearer and focusing on the value of religion or modesty. A questionnaire has been conducted by online email and social media and has collected the total of 507 answers of Indonesian young women. Data analysis methodology is correlation analysis, linear and multiple regression analysis. The results suggests that purchase intention has been positively affected by luxury brand perception and brand love while the relationship between brand coolness and purchase intention has been rejected. Moreover, there is also a positive relationship between brand coolness and brand love, purchase intention and word of mouth, and brand love and word of mouth.